Inversion of Configuration at the Phosphorus Nucleophile in the Diastereoselective and Enantioselective Synthesis of P‐Stereogenic syn‐Phosphiranes from Chiral Epoxides. Issue 18 (23rd March 2018) - Muldoon, Jake A.; Varga, Balázs R.; Deegan, Meaghan M.; Chapp, Timothy W.; Eördögh, Ádám M.; Hughes, Russell P.; Glueck, David S.; Moore, Curtis E.; Rheingold, Arnold L.
Abstract: Nucleophilic substitution results in inversion of configuration at the electrophilic carbon center (SN 2) or racemization (SN 1). The stereochemistry of the nucleophile is rarely considered, but phosphines, which have a high barrier to pyramidal inversion, attack electrophiles with retention of configuration at P. Surprisingly, cyclization of bifunctional secondary phosphine alkyl tosylates proceeded under mild conditions with inversion of configuration at the nucleophile to yield P‐stereogenic syn ‐phosphiranes. DFT studies suggested that the novel stereochemistry results from acid‐promoted tosylate dissociation to yield an intermediate phosphenium‐bridged cation, which undergoes syn ‐selective cyclization. Abstract : Nucleophilic substitution results in inversion (SN 2) or racemization (SN 1) at the electrophile, but what about the nucleophile? P‐Stereogenic phosphines act as nucleophiles with retention of the configuration at phosphorus. In the first reversal of this paradigm, intramolecular nucleophilic substitution with inversion at phosphorus is key in controlling the diastereo‐ and enantioselective synthesis of P‐stereogenic syn ‐phosphiranes.